Impairment in activities of daily living and readmission in older patients with heart failure: a cohort study - Tu Ngoc Nguyen; Tan Van Nguyen; Huyen Thanh Dang; Mason Jenner Burns; Hiep HH Dao (BMJ Open)
Objectives This study aims to investigate the prevalence of impairment of activities of daily living (ADLs) in older patients with heart failure (HF), and to examine the impact of ADL impairment on readmission after discharge.Design and settings A prospective cohort study was conducted in patients aged ≥65 years with HF admitted to a tertiary hospital in Vietnam from August 2016 to June 2017. Difficulties with six ADLs were assessed by a questionnaire. Participants were classified into two categories (with and without ADL impairment). The associations of ADL impairment with 3-month readmission were examined using logistic regression models.Results There were 180 participants (mean age 80.6±8.2, 50% female) and 26.1% were classified as having ADL impairment. The most common impaired activity was bathing (21.1%), followed by transferring (20.0%), toileting (12.2%), dressing (8.9%), eating (3.3%), and continence (2.8%). During 3-month follow-up, 32.8% of the participants were readmitted to hospitals (55.3% in participants with ADL impairment, 24.8% in those without ADL impairment, p<0.001). ADL impairment significantly increased the risk of 3-month readmission (adjusted OR 2.75, 95% CI 1.25 to 6.05, p=0.01).Conclusions In summary, ADL impairment was common in older hospitalised patients with HF and was associated with increased readmission. These findings suggest further studies on ADL assessment and intervention during transition care for older patients with HF after discharge to prevent readmission.